KUAT LENTUR PANEL PARTISI DARI LIMBAH STYROFOAM YANG DILAPISI KAWAT LOKET - Dewi Sulistyorini (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2015)
The room is one element in a building. So, we need a wall or divider as a separator between the room. Partition wall was designed as a temporary partition wall and without the loaded. Building materials must have some advantages such as light weight, durability, shape can suit the needs, the speed of the construction, low cost and environmental friendly. Such materials like Styrofoam or expanded polysterene (EPS), which is an insulator lightweight material, rigid and made from plastic materials. Partition panel research of styrofoam waste coated wiremesh is an attempt to determine the potential use of styrofoam waste as a partition panel that reviewed material from the unit weight and flexural strength. Test specimen for 3 (three) pieces of panels with dimension 80 cm long, 30 cm wide, 1 cm thick, with compression 2 MPa and water-cement factor 0.45. The weight of used cement 250 kg / m3, wiremesh diameter of 0.6 mm with grid 6 mm x 6 mm. The test results obtained average unit weight for panel was 1081.9 kg / m3 and average flexural strength of 0.721 MPa. The pattern of the damage indicated by the curved wiremesh prior to the loading position, and then styrofoam concrete cracks